Endocrine Regulation on Bone by Thyroid - Zhu, Siyuan; Pang, Yidan; Xu, Jun; Chen, Xiaoyi; Zhang, Changqing; Wu, Bo; Gao, Junjie (Frontiers in Endocrinology, 2022)
Background As an endocrine organ, the thyroid acts on the entire body by secreting a series of hormones, and bone is one of the main target organs of the thyroid. Summary This review highlights the roles of thyroid hormones and thyroid diseases in bone homeostasis. Conclusion Thyroid hormones play significant roles in the growth and development of bone, and imbalance of thyroid hormones can impair bone homeostasis.